2001
DOI: 10.1046/j.1440-1746.2001.02476.x
|View full text |Cite
|
Sign up to set email alerts
|

Profile of hepatocellular carcinoma in India: An insight into the possible etiologic associations

Abstract: In India: (i) HBV infection is the predominant factor for the development of HCC, often related to mutant forms of HBV; (ii) a majority of the HCC patients have overt cirrhosis of the liver; and (iii) HCV and alcohol per se are uncommonly associated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
58
5
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 29 publications
11
58
5
1
Order By: Relevance
“…13 However, we found that irrespective of the degree of differentiation, the tumor cells were nonpermissive. Our finding of 100% nuclear integration is in contrast to the finding of Sarin et al, 9 who found integration in only 59% of the cases by genomic Southern blot hybridization. The low percentage of integration observed in their study could be attributed to the technique used, as shown by the titration studies of Shintani et al 23 An in situ hybridization study in HBsAg-positive Chinese patients with HCC revealed the integrated virus in 72% and the episomal state in 19% of patients.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…13 However, we found that irrespective of the degree of differentiation, the tumor cells were nonpermissive. Our finding of 100% nuclear integration is in contrast to the finding of Sarin et al, 9 who found integration in only 59% of the cases by genomic Southern blot hybridization. The low percentage of integration observed in their study could be attributed to the technique used, as shown by the titration studies of Shintani et al 23 An in situ hybridization study in HBsAg-positive Chinese patients with HCC revealed the integrated virus in 72% and the episomal state in 19% of patients.…”
Section: Discussioncontrasting
confidence: 99%
“…8 The relatively lower prevalence observed by Sarin et al 9 may have been due to the lower sensitivity of dot blot hybridization compared with PCR, which was used in the earlier study. 8 The difference between their study 9 and our current study could be due to a difference in the prevalence of the virus in North India versus South India. Alternatively, the difference could also be ascribed to the differences in the sensitivities of the dot blot and in situ hybridization tests.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations